Angular phase-shifting interferometry for surface shapes measurement using vortex beam. (July 2023) - Yang, Dong; Zhang, Yanfeng; Yang, Zhongming
Highlights: In this research, we proposed a novel optical surface shapes measurement method based on conformal mapping-angular phase-shifting interferometry. It paves the way for the application of vortex beams in the field of optical surface shape measurement. It is of great significance to the miniaturization design of high-precision interferometers, and can significantly reduce the experimental cost. We use a Q-plate in the reference optical path to introduce a 90-degree phase shift, and conformal mapping is used to demodulate the surface shape. This method not only ensures the accuracy of surface shape measurement; but also avoids the use of expensive precision translation stages; and has specific anti-vibration performance. The measuring device is simple, compact, easy to operate and low cost. Abstract: We proposed a novel optical surface shapes measurement method based on conformal mapping-angular phase-shifting interferometry (APSI). This method rotates a Q-plate in the reference light path to introduce a 90-degree phase shift. The mathematical tool of conformal mapping is used for surface shape demodulation. After removing the helical phase in the compound phase, high-precision surface shape measurement results are obtained, and the measurement surface shape deviations are 3.33 nm (PV) and 0.26 nm (RMS). This work paves the way for surface shape measurement and compound phase demodulation using vortex beams.